1999
DOI: 10.1111/j.1348-0421.1999.tb02439.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy and Immunogenicity of Vi‐Porin Conjugate against Salmonella typhi

Abstract: A conjugate vaccine against Salmonella typhi was prepared by covalently binding capsular polysaccharide (Vi) with porin, both isolated from S. typhi. First, Vi and porins were extracted. The Vi was purified from S. typhi Ty2. The purified Vi conformed to the requirements of the World Health Organization. Porins were purified from S. typhi 0901. The Vi was bound to the porins by a heterobifunctional cross‐linking reagent, N‐succinimidyl‐3‐(2‐pyridyl dithio)‐propionate (SPDP). After preparing the Vi‐porin conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In an earlier study, a conjugate of Vi bound to porin was shown to induce both systemic and mucosal immune responses, which were protective against challenge with S. typhi (Singh et al, 1999). A higher level of anti-Vi IgG on coupling of Vi to rEPA was noticed in 5-to 14-year-old children (Kossaczka et al, 1999).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In an earlier study, a conjugate of Vi bound to porin was shown to induce both systemic and mucosal immune responses, which were protective against challenge with S. typhi (Singh et al, 1999). A higher level of anti-Vi IgG on coupling of Vi to rEPA was noticed in 5-to 14-year-old children (Kossaczka et al, 1999).…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, conjugates have been made by chemical coupling of Vi antigen with P. aeruginosa recombinant exoprotein A (rEPA) as the carrier (Kossaczka et al, 1999;Lin et al, 2001). Another approach has been to conjugate Vi to porins isolated from the same organism (Paniagua et al, 1992;Singh et al, 1999). In the present study we have conjugated the Vi antigen to IROMPs, as the latter have been shown to be protective in Gram-negative infections (Banerjee-Bhatnagar & Frasch, 1990;Chibber & Bajaj, 1995).…”
Section: Discussionmentioning
confidence: 94%
“…This notable immunogenicity of porins to sustain bactericidal antibody memory response could be explained by either of the following non‐exclusive mechanisms. First, because salmonella porins are good immunogens 20,21 , 27,33 , 36–42 and porins from other pathogens have been identified as TLR2 agonists 29–31 . Thus, during the initial immune response, it is possible that salmonella porins might be simultaneously recognized by B‐cell receptors and innate receptors, such as TLRs, thereby inducing the differentiation of naive B cells into effector antibody‐secreting plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the ability of porins to elicit a host immune response and thus protection of the host against infection, our group and others have studied porins from S. typhi as candidates for a vaccine against typhoid fever, 20,21 a life‐threatening systemic disease that remains an important health problem in some developing countries 22 . With up to 10 5 molecules per cell, porins are the most abundant proteins found in the outer membrane of Gram‐negative bacteria; porins assemble in trimers and form stable pores that allow the passive transport of nutrients 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella and other Gram-negative bacteria express outermembrane proteins (Omps) that are highly immunogenic and elicit innate and adaptive immune responses in mice (9)(10)(11)(12)(13)(14). In humans, IgG and IgM Abs against pore-forming Omps (porins) can be found in individuals recovering from typhoid fever (15,16).…”
mentioning
confidence: 99%